Green Accounting, Leverage, and Cash Holding: Key Factors in Determining Firm Value - Dini Wahjoe Hapsari; Renaldy Febiana; Muna Norkhairunnisak Ustadi (Jurnal Ilmiah Akuntansi, 2024)
The impact of green accounting, leverage, and cash holding on firm value in the Indonesian energy sector, particularly how these factors interact and influence both environmental and financial outcomes, remains underexplored. This study aims to bridge this gap by examining the effects of green accounting, leverage, and cash holding on firm value, thus providing valuable insights that could influence investor decisions. Utilizing a purposive sampling method, this research analyzes data from 75 companies within the sector. The findings reveal that maintaining optimal cash holdings is crucial, as it can maximize company profits and enhance firm value. Conversely, the implementation of green accounting varies significantly across companies in the energy sector, which means it does not consistently impact firm value in a significant way. This suggests that while green accounting practices are gaining traction for their potential environmental benefits, their direct influence on financial valuation is not uniformly perceived. Furthermore, leverage, as measured by the debt-to-equity ratio, shows that the use of external funding does not significantly affect investors’ perceptions of firm value.